Heidegger’s Critical Confrontation with the Concept of Truth as Validity - Fahmy-Hooke Joshua (Open Philosophy)
My primary goal in this article is to provide a historical reconstruction of Heidegger’s relationship to Hermann Lotze’s logic of validity (Logik der Gültigkeit). Lotze’s characterization of truth’s “actuality” solidifies the fallacious presupposition that the essence of truth is to be understood primarily in terms of logical assertions. In Heidegger’s view, the predicates “true” and “false,” as the paradigmatic attributes of propositions and judgments, are derivatives of a fundamental and “primary being of truth” known as disclosedness (Erschlossenheit). Heidegger marks this decisive position in §44 of Being and Time and gains its methodological purchase by deconstructing traditional logic (kritischer Abbau der überlieferten Logik). Heidegger’s treatment, however, is abbreviated, and his sources remain notoriously concealed. For this reason, much is to be gained by examining the supplement provided one year earlier in a lecture course titled Logic: The Question of Truth (WS 1925–26). Heidegger devotes nearly 100 pages to the contemporary situation of philosophical logic. In this course, Heidegger critically evaluates a core principle of both phenomenology and neo-Kantian Erkenntnistheorie: the concept of validity (Geltung). This term originates from Lotze’s Platonic Ideenlehre, which asserts that Platonic “ideas” correspond to thoughts through a logical necessity. Consequently, they are deemed valid and eternally self-identical but do not need to exist in the world. For the purposes of this study, I show the historical significance and influence of Lotze’s Logic on twentieth-century Neo-Kantianism and Phenomenology. I provide a detailed account of Lotze’s interpretation of the Platonic theory of ideas, which supports his theory of validity. By returning to Lotze’s text, I provide an in-depth review of Heidegger’s reading of Lotze, whom he charges with misleading twentieth-century epistemology. If successful, this article provides the necessary and historical context to understand what is left unsaid and concealed in §44 of Being and Time. This article also serves the auxiliary purpose of acting as a prolegomenon for Heidegger’s urgent return to Aristotle’s thought and accurately determining the essence of truth.